Teaching Reading Comprehension through Request Procedure to the Tenth Grade Students of SMA Olaraga Negeri Sriwijaya Palembang - Meli Damayanti (ELTE Journal (English Languange Teaching and Education), 2015)
Abstract           This study was conducted to find out whether or not it is effective teaching reading comprehension achievement through Request Procedure to the tenth grade students of SMA Negeri Olahraga Sriwijaya Palembang. The samples of this study were the tenth grade students of SMA Negeri Olahraga Sriwijaya Palembang in the academic year of 2013-3014. The primary data were collected by means of test and it was analyzed by match t-test. The results show that the students’ reading comprehension achievement improved after treatment. The mean score of the students’ pre test was 65.35 and post test was 77.39. The analysis of t-test calculation shows that the value of t was 10.684. Then the value of the t-table was 2.086 at the significance level of 0,05% with df  of 22.  The findings point that t-obtained was higher than t-table. It implies that Request Procedure was effective teaching reading comprehension to tenth grade students of SMA Olhraga Negeri Sriwijaya Palembang Key words: Reading comprehension, Request Procedure